PENYULUHAN HUKUM TENTANG PENGANGKATAN ANAK MENURUT HUKUM ISLAM DI DESA GANDATAPA, KECAMATAN KEDUNGBANTENG, KABUPATEN BANYUMAS - Priyadi, Aris; Suryati, Suryati; Anindito, Teguh (WIKUACITYA: Jurnal Pengabdian Kepada Masyarakat, 2025)
Marriage is an inner and outer bond between a man and a woman as husband and wife with the aim of forming a happy and eternal family (household) based on the belief in the Almighty God." From this formulation it can be concluded that from marriage it is hoped that offspring (children) will be born as successors in the family, so that parents are obliged to care for and educate them so that they grow and develop naturally in the family and community environment. The presence of a child is something that is highly desired. The happiness and harmony of a family is marked by the birth of a child, because one of the purposes of marriage is to continue offspring. As Allah SWT says in Surah An-Nahl 72, namely: Meaning: "Allah made for you a mate (wife) from yourself (your nation) and made children and grandchildren from your wife, and gave good sustenance, whether they believe which is false (not true) and denies Allah's blessings (Q.S. An-Nahl Verse 72). If a married couple cannot have children during their marriage, then they can also continue their descendants so that the tribe/clan does not become extinct by adopting children or what is often called adoption. Therefore, the purpose of adopting a child is, among other things, to continue the offspring, when in a marriage there are no children. This is one way out and a positive and humane alternative to the presence of a child in the arms of the family. In order for members of the community to know and understand more about adoption, the rights and obligations of parents and adopted children, one of the efforts is to hold legal education regarding adoption.